Perceived stress and mobile phone addiction among college students: The roles of self-control and security - Zhang, Anqi; Xiong, Sicheng; Peng, Yu; Zeng, Yixin; Zeng, Chengwei; Yang, Ying; Zhang, Bin (Frontiers in Psychiatry, 2022)
Objective: According to the General Strain Theory, stress can lead to a range of problem behaviors. In the current study we focused on the association between perceived stress and mobile phone addiction. We hypothesized that this association is mediated by low self-control, and that the first path of the mediation is moderated by security. Methods: College students (N = 397; ages 16 to 21; 51.89% females) from a university in Hunan Province, China were surveyed by cluster sampling method. The students completed the Smartphone Addiction Scale-Short Version (SAS-SV), the Depression Anxiety Stress Scale (DASS-21), the Self-Control Scale (SCS), and the Security Questionnaire (SQ) during regular class time. SPSS26.0 statistical software was used for descriptive statistics and Pearson correlation analyses, the SPSS macro PROCESS was used to test the mediating effects of self-control and the moderating role of security. Results: Mediation analysis showed that as expected, perceived stress was associated with lower self-control, which in turn was associated with a higher risk for mobile phone addiction. Also as expected, moderated mediation analysis indicated that the association between perceived stress and self-control was moderated by security. Specifically, the relationship between perceived stress and self-control was stronger for low security. Conclusion: This study provides useful insight into the understanding of how perceived stress increases the risk of mobile phone addiction. The results consistent with the General Strain Theory and further indicate that concrete approaches are required for the prevention and intervention to reduce mobile phone addiction among college students.